Flexible foraging for finding fish: variable diving patterns in Magellanic penguins Spheniscus magellanicus from different colonies - Sala, Juan Emilio (2014)
Seabirds have to deal with environmental variability and are predicted to modulate foraging behavior to maximize fitness, with particularly strong selection pressure for optimal behavior during chick provisioning when energy demands are high. We reported data from 42 breeding birds equipped during the early chick-rearing period with depth recorders at four different colonies [Punta Norte (42°S), Bahía Bustamante (45°S), Puerto Deseado (47°S) and Puerto San Julián (49°S)] in patagonian Argentina. Although Magellanic penguins are purported to show little flexibility in foraging behavior, we discovered marked inter-colony differences in diving behavior. Even though the southern marine ecosystems, in general, and the area exploited by Magellanic penguins from the studied colonies, in particular, are usually characterized by their stability, we cannot entirely exclude that interannual differences may have also affected our results. The colonies located in the center of the breeding distribution, Bahía Bustamante and Puerto Deseado, showed the greatest diving and foraging effort with Bahía Bustamante penguins having the deepest and longest dives of all birds and requiring the longest post-dive recovery durations at the surface. Puerto Deseado had the birds with the highest values of diving effort parameters. Penguins from both colonies also had the highest descent and ascent rates during dives. We assume that the clear variation in diving behavior reflects the response of the birds to the varying prey types and availability around the different colonies, but note that, despite this, some colonies fare markedly better than others in breeding.